Application of Pursed Lip Breathing to Changes in Oxygen Saturation on Chronic Obstructive Lung Disease in Sitanala Hospital at Tangerang - Khairunnisa Bakhitah; Toto Subiakto (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
Background: Chronic Obstructive Pulmonary Disease (COPD) is the third most common cause of death in the world. The prevalence of COPD in Banten Province is 6.3%. COPD patients experience inspiratory muscle weakness and muscle dysfunction that contribute to shortness of breath. One of the effective breathing exercises in handling shortness of breath is pursed lips breathing (PLB) which is a breathing exercise technique that involves breathing through the resistance caused by the narrowing of the lips can improve gas currency which can be seen by improving arterial oxygen saturation. Purpose: To identify the benefits of using pursed lip breathing in increasing oxygen saturation in cases of gas disturbances in patients with Chronic Obstructive Pulmonary Disease. Method: The method used is to carry out nursing care for COPD patients with gas transaction disorder problems. Result: The results have been analyzed that giving pursed lip breathing exercises for 3 days with a time of ± 15 minutes can increase oxygen saturation in Mrs.L from SPO2: 94% to SPO2: 97% and in Mr.N from SPO2: 92% to SPO2: 95%.